ANALISIS POTENSI EKONOMI KABUPATEN MAGELANG TAHUN 2012-2017 - Kholidur Rizki; Whinarko Juliprijanto; Rian Destiningsih (Universitas Tidar, 2019)
In the implementation of development in Magelang Regency, it cannot be separated from the support of existing regional potential. The potential of the area is explored and utilized as much as possible so that it can increase development. The purpose of this study is to identify the basic sectors in Magelang, knowing the dominant growth sector and sector with a high contribution in Magelang Regency, and knowing the potential economic sectors in Magelang Regency during 2012-2017. As well as the efforts of the Magelang Regency government in supporting the development of economic potential to strengthen the economy and community welfare. The data used in this study are secondary data in the period 2012-2017. It is sourced from the Central Statistics Agency (BPS) of Magelang Regency and Central Java Province. From the data obtained from BPS, what will be used is the GRDP data of Magelang Regency and Central Java Province GRDP to analyze the state of the economic sector can be done by quantitative descriptive method through the Location Quotient (LQ) analysis, Growth Ratio Method (MRP) and Overlay analysis. The results of this study state that by using LQ analysis it will be known the base economic sector, MRP analysis to find out the dominant growth of the economic sector, while the Overlay analysis to determine the magnitude of economic sector growth and to determine the size of the sector contributing to Magelang Regency GRDP. So with that potential sector will emerge in Magelang Regency. It can be concluded that in Magelanag Regency during 2012-2017 there were (1) 11 basic economic sectors, (2) 10 economic sectors with high growth and good contributions, (3) 6 potential economic sectors.